O poder de denúncia do cordel no cinema: O romance do vaqueiro voador, de João Bosco Bezerra Bonfim e Manfredo Caldas - Sylvie Debs (Estudos de Literatura Brasileira Contemporânea)
The movie O romance do vaqueiro voador, by Manfredo Caldas, is built departing from the homonymous cordel by João Bosco Bezerra Bonfim – which, on its turn, was inspired by the documentary Brasília segundo Feldman, by Vladimir Carvalho – aiming to tell, denounce and remember the tragedy the building of the city was. This article aims to discuss some questions: why choose as a character a pot cowboy to wander in the places of the tragedy? Why use a cordel to give origin to another movie?